2009
DOI: 10.1017/s0022215109005155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tympanic membrane perforation on middle-ear sound transmission

Abstract: Tympanic membrane perforation causes a sound conduction disturbance, and the size of this conduction disturbance is proportional to the perforation area. However, precise evaluation of perforation size is difficult, and there are few detailed reports addressing this issue. Furthermore, such evaluation becomes more difficult for irregularly shaped perforations. This study conducted a quantitative evaluation of tympanic membrane perforations, using image analysis equipment.A significant correlation was found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 19 publications
5
41
2
Order By: Relevance
“…Bhusal et al, [22] observed that hearing loss is greater in lower frequency when compared with higher frequencies, for all sites of perforation. Matsuda et al, [23] observed frequency dependence of hearing loss and the highest hearing threshold was of the perforations in anteroinferior quadrant.…”
Section: Effect Of Sizementioning
confidence: 96%
“…Bhusal et al, [22] observed that hearing loss is greater in lower frequency when compared with higher frequencies, for all sites of perforation. Matsuda et al, [23] observed frequency dependence of hearing loss and the highest hearing threshold was of the perforations in anteroinferior quadrant.…”
Section: Effect Of Sizementioning
confidence: 96%
“…Chronic suppuration can occur with or without cholesteatoma, and the clinical history of both conditions can be very similar. The treatment plan for cholesteatoma always includes tympanomastoid surgery with medical treatment as an adjunct [2,3] . Therefore, the clinician treating chronic otitis media must always have a high index of suspicion in order not to miss a critical diagnosis.…”
Section: Aim Of Work: Evaluation the Role Of Multi-detectormentioning
confidence: 99%
“…Perforations on a location directly lateral to the round window were considered to increase sound pressure around the round window to a larger extent than perforations on other locations of the TM, resulting in a reduction of sound pressure difference between the oval and round windows. Ahmad et al (9) observed a larger CHL below 1500 Hz in patients with TM perforations on the posterior-inferior parts of the TM, and Masuda et al (10) found the largest CHL in patients with TM perforations on the anterior-inferior quadrant compared to the other quadrants of the TM. By contrast, significant correlation between location of the TM perforation and CHL was not observed in other clinical (6,7), and experimental studies (5,11).…”
Section: Introductionmentioning
confidence: 98%